Do two- and three-dimensional imaging show the same risk of nerve injury during extraction of mandibular third molars depending on their angulations and distances to the inferior alveolar canal? - A retrospective clinical study over 8 years - Oliver Meller; Florian Pfaffeneder-Mantai; Benedikt Schneider; Dragan Ströbele; Wilhelm Frank; Dritan Turhani (Elsevier, 2022)
Objectives: Injury of the inferior alveolar canal (IAC) is a common complication during mandibular third molar (MTM) surgery. The aim of this study was to compare the MTM risk assessment using orthopantomography (OPG) and cone beam computed tomography (CBCT) images showing different MTM angulations and distances to the IAC. Materials and methods: This retrospective study investigated 388 lower third molars of 259 patients radiologically over eight years using OPG and CBCT. Measurement and categorisation of MTM position showed four different types of angulations: vertical (type 1), mesioangular (type 2), horizontal (type 3) and distoangular (type 4). The shortest distance from the MTM and the IAC was measured and categorized after a risk classification (class 1-3) for injury of the IAC. Results: High risk (class 1) was detected in 38.4%, moderate risk (class 2) in 21.9%, and low risk (class 3) in 36.1% using OPG data. In CBCT, high risk (class 1) was found in 11.6%, moderate risk (class 2) in 5.7%, and low risk (class 3) was fount in 78.6%. The same risk classification for OPG and CBCT was present in 25.1% of cases. The most common angulation was type 1 in 49.7%, followed by type 2 in 40.5%, 5.2% in type 3, and 4.4% in type 4. Conclusion: Preoperative CBCTs are essential for risk evaluation and treatment planning in MTM surgery due to differences in OPG and CBCT data regarding nerve injury risk.